ASSISTANCE OF CODING EXTRACURRICULAR PROGRAM AT SD ANAK PANAH KENJERAN - Rudi Santoso; Agus Dwi Churniawan (Universitas Airlangga, 2022)
Basic programming training and assistance for Elementary School at SD Kr. Anak Panah are an urgent need. This is caused by the demands of students to develop their potential. Elementary students Kr. Anak Panah requires an increase in skills in terms of making or coding basic games. This training aims to improve the basic abilities of elementary school (SD) in terms of information technology. Training for students to meet the need for basic and high-level coding mastery for elementary school age children. The training was conducted online for 5 (five) months involving 200 Elementary School (SD) students. The final result of the training showed an increase in students' competence in terms of game programming coding. Basic level. Meanwhile, the average ability of the trainees increased from level 4th (four) to level 8th (eight) from a scale of 1 – 10.